2016
DOI: 10.1039/c5cc09699e
|View full text |Cite
|
Sign up to set email alerts
|

In situ grown, self-supported iron–cobalt–nickel alloy amorphous oxide nanosheets with low overpotential toward water oxidation

Abstract: Electrocatalytic water oxidation by in situ grown iron-cobalt-nickel ternary alloy amorphous oxides is reported. This catalytic material was prepared by simple anodization of an alloy plate followed by low-temperature annealing, which shows superior electrocatalytic activity toward oxygen evolution reaction with an overpotential of only 170 mV and a low Tafel slope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 32 publications
(12 reference statements)
1
54
0
1
Order By: Relevance
“…The former corroborates the existence of Mo VI -O, 10 and the latter indicates the presence of a great number of defect sites with low oxygen coordination on the surface of the etched Co/Mo; such sites have been reported to be favourable for high catalytic activity. [15][16][17][18] The Mo 3d spectrum (Fig. 2d) shows a characteristic doublet of Mo VI at 232.1 eV (Mo 3d 5/2 ) and 235.4 eV (Mo 3d 3/2 ), 6,19 indicating that the surface Mo was also oxidized by CAN.…”
Section: Resultsmentioning
confidence: 99%
“…The former corroborates the existence of Mo VI -O, 10 and the latter indicates the presence of a great number of defect sites with low oxygen coordination on the surface of the etched Co/Mo; such sites have been reported to be favourable for high catalytic activity. [15][16][17][18] The Mo 3d spectrum (Fig. 2d) shows a characteristic doublet of Mo VI at 232.1 eV (Mo 3d 5/2 ) and 235.4 eV (Mo 3d 3/2 ), 6,19 indicating that the surface Mo was also oxidized by CAN.…”
Section: Resultsmentioning
confidence: 99%
“…The faster electron transfer is due to the synergistic effect from the multiple transition metals, as well as other factors. It is well consistent with earlier results …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, there has been a shi from utilising crystalline catalysts to producing amorphous materials for water splitting. 22,[25][26][27] A recent study has shown that a photochemical metal-organic deposition process can produce amorphous mixed metal oxides displaying activity for the OER. 22 Crystallinity or lack thereof is therefore expected to be a critical factor in determining the activity of the catalyst as evidence is now emerging that a reversible crystalline to amorphous transition can occur during the OER, as reported for Co 3 O 4 .…”
Section: Introductionmentioning
confidence: 99%